Fiscal Policy, Labor Unions, Competitiveness and Monetary Institutions: Their Long Run Impact on Unemployment, Inflation and Welfare - Alex Cukierman; Alberto Dalmazzo (Kiel Institute for the World Economy (IfW), 2007)
OBJECTIVES AND MOTIVATION: This paper considers the impact of interactions between competitiveness, fiscal policy and monetary institutions in the presence of unionized labor markets on economic outcomes and welfare in the long run. Two main classes of questions are investigated. First, what is the impact of exogenously given labor taxes and unemployment benefits on the choice of monetary policy by the central bank, on the choice of nominal wages by unions, on the choice of prices by monopolistically competitive firms and through them on unemployment, inflation and welfare? A related question is, how does the level of competitiveness on goods? market affect the economy and welfare? Second, how are labor taxes and redistribution chosen by a (Stackelberg leader) fiscal authority whose objectives are a weighted average of social welfare and of catering to the interests of political supporters, and how does the general equilibrium induced by this choice affect welfare? The framework of the paper is motivated by the European scene in which the fraction of the labor force covered by collective agreements dominates wage setting in the labor market. 'PLAYERS' AND PAYOFFS: The model economy features labor unions that maximize the expected real income of union members over states of employment and of unemployment, a central bank that strives to minimize the combined costs of inflation and of unemployment, and a continuum of monopolistically competitive firms, each of which maximizes its profits. The last part of the paper also features a fiscal authority that sets taxes and redistribution so as to maximize a combination of social welfare and of benefits to particular constituencies. Utility from consumption is characterized by means of a CES, Dixit-Stiglitz, utility function and (as in Sidrauski type models) money appears in the utility function. METHODOLOGY AND 'PLAYERS' STRATEGIES: The first question is investigated within a three stage game in which labor unions move first and commit to nominal wages and the central bank moves second and chooses the money supply. In the third and last stage each of a large number of monopolistically competitive firms picks its price. To deal with the second class of questions the game is expanded to feature a preliminary stage in which government chooses labor taxes and redistribution anticipating the subsequent responses of the other players. General equilibrium is characterized and used to find the impact of various economic and institutional parameters.
Keywords: 330